Ammonium thiosulfate as blossom thinner in 'Maxi Gala' apple trees - Lucas De Ross Marchioretto; Andrea De Rossi; Micheli Fochesato Michelon; Julio Cesar Orlandi; Leonardo Oliboni do Amaral (Pesquisa Agropecuária Brasileira, 2018)
Abstract: The objective of this work was to evaluate the feasibility of using ammonium thiosulfate as a chemical blossom thinner in 'Maxi Gala' apple (Malus domestica) trees and its effects on fruit quality. The experiment was carried out in an experimental orchard in the Southern Brazil, in a randomized complete block design, with five replicates. Ammonium thiosulfate was sprayed on the apple trees at the full bloom stage, at 0, 1.5, 2.5, and 3.5%. Evaluations were performed for the effects on crop load, fruit set, yield efficiency, and fruit quality parameters such as weight, shape, total soluble solids, seed number, flesh firmness, color, and russeting occurrence. Ammonium thiosulfate at 2.5% is effective to reduce crop load and to improve fruit quality. The thinning effect of ammonium thiosulfate is not dependent on the weather conditions during the crop season. The rate of 3.5% of ammonium thiosulfate causes overthinning and does not result in the improvement of fruit quality.